An Exploration of the Effect of Incremental and Radical Innovations on Customer Relationships in Service Sectors: A Case Study of New Services From a Taiwanese Bank - Tsai, Ming San (2014)
Innovation and customer relationships have been increasingly regarded as two critical elements to achieve long-term success for companies. These two elements are relatively important in service industry, as a result that both service innovation and customer relationships are closely related to the interaction between customers and suppliers in service sectors. However, few articles discussed the issues by integrated these two notions. This research is aimed to understand the nature of changes in the relationship between customers and suppliers caused by the introduction of new services, and explore the impacts due to different types of new services. A case study research on a Taiwanese bank was selected to study the changes in customer relationships after the launch of new financial services. According to the results, the effects of new financial services on customer relationships are presented in three dimensions, which are relationship drivers, relationships constructs and role of employees. Further, trust is related to the supplier itself instead of new services. This research also found that the effects on customer relationships are varied in terms of radical innovations and incremental innovations. Therefore, companies should be aware of different impacts on customer relationships when implementing service innovations.